2005
DOI: 10.3354/dao063231
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of the haemocyte parasite Bonamia sp. in flat oysters Ostrea puelchana farmed in San Antonio Bay (Argentina)

Abstract: Culture of native flat oysters Ostrea puelchana d'Orbigny in San Antonio Bay (San Matías Gulf, Argentina) began in 1995. After elevated mortality (33%) occurred in September 1996, 18 mo after immersion, histopathological analysis and evaluation of parasitic prevalence was carried out. In October 1997, after 31 mo of cultivation, cumulative mortality was 80%, and in December of the same year, when individuals reached marketable size, mortality was 95% and culture was discontinued. The present study describes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Moreover, the DNA sequence analysis supported, in 2 samples, the occurrence of microcells belonging to B. exitiosa, thus corroborating the recent report of this species in European flat oysters (Abollo et al 2008). B. exitiosa is known to infect O. chilensis in New Zealand (Dinamani et al 1987) and O. angasi in Australia (Hine & Jones 1994, Hine 1996, Corbeil et al 2006, while other parasites, referred to as B. exitiosa (Lopez-Flores et al 2007), have been reported in O. chilensis in Chile (Campalans et al 2000), in O. puelchana in Argentina (Kroeck & Montes 2005), and in Crassostrea ariakensis in North Carolina, USA ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the DNA sequence analysis supported, in 2 samples, the occurrence of microcells belonging to B. exitiosa, thus corroborating the recent report of this species in European flat oysters (Abollo et al 2008). B. exitiosa is known to infect O. chilensis in New Zealand (Dinamani et al 1987) and O. angasi in Australia (Hine & Jones 1994, Hine 1996, Corbeil et al 2006, while other parasites, referred to as B. exitiosa (Lopez-Flores et al 2007), have been reported in O. chilensis in Chile (Campalans et al 2000), in O. puelchana in Argentina (Kroeck & Montes 2005), and in Crassostrea ariakensis in North Carolina, USA ).…”
Section: Discussionmentioning
confidence: 99%
“…B. perspora is a newly described protozoan species found in Ostreola equestris (North Carolina, USA) and represents the first Bonamia species producing a typical haplosporidian spore (Carnegie et al 2006). Other B. exitiosa-like organisms have been described in O. chilensis from Chile (Kern 1993, Campalans et al 2000, O. puelchana from Argentina (Kroeck & Montes 2005), and Crassostrea ariakensis from North Carolina ); these organisms have been subsequently declared B. exitiosa (Lopez-Flores et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other isolates of Bonamia have been reported from O. chilensis in Chile (Campalans et al 2000), Crassostrea ariakensis in North Carolina (Burreson et al 2004) and O. puelchana in Argentina (Kroeck & Montes 2005). Taxonomic relationships between these isolates and described species within the genus need to be established.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 96%
“…This is particularly true since recent reports of Bonamia sp. Zealand and Australia have significantly broadened the recognised geographical distribution of this parasite (Campalans et al 2000, Burreson et al 2004, Kroeck & Montes 2005. With regards to those recent isolates from Chile, the USA and Argentina, it is believed that the sequence data provided in this paper will help to clarify taxonomic relationships within the genus Bonamia and, more particularly, the species B. exitiosa.…”
Section: Resultsmentioning
confidence: 97%
“…Subsequent molecular characterisation and sequencing of the small subunit (ssu) rRNA operon of Bonamia species confirmed the broad northern hemisphere distribution of B. ostreae (Carnegie et al 2000, Cochennec et al 2000. Conversely, since its redesignation as B. exitiosa , the exact distribution and geographical range of this antipodean Bonamia is unclear (Hine 1996, Campalans et al 2000, Burreson et al 2004, Kroeck & Montes 2005, but this information is of central importance to better address management of disease caused by this serious pathogen (OIE 2003). Sequence comparison of the 18S gene and Internal Transcribed Spacer 1 (ITS-1) region of the ssu rRNA operon has helped clarify the taxonomic position of these intra-haemocytic parasites and has led to the development of diagnostic methods capable of detecting and distinguishing different isolates -resources essential for the development of health surveillance, disease monitoring and oyster stock translocation programmes .…”
Section: Introductionmentioning
confidence: 99%